LEGAL STUDY OF ECO-COMMUNITY WASTE MANAGEMENT CONCEPTS THROUGH THE DEVELOPMENT OF ECO ENZYME AS A SOLUTION WASTE MANAGEMENT IN POPULAR CITY - Mas Subagyo Eko Prasetyo (Jurnal Multidisiplin Sahombu, 2021)
Garbage is discarded and unused goods and only takes up space to be accommodated and causes human health to decline over time, and as a result of the impact of waste that has no value and will only add to problems when its management is not appropriate. According to Law Number 18 of 2008 concerning Waste Management (Waste Law) it is stated that district/city governments have an obligation to manage waste properly and with an environmental perspective and improve waste management from an open dumping system to a sanitary landfill system. The type of research carried out in this research is normative legal research, which is a scientific research procedure carried out to find the truth based on scientific logic from the normative side, then the results of this study explain that, In Indonesia, regulations regarding waste management are regulated in various laws and regulations that applies starting from the 1945 Constitution of the Republic of Indonesia, the Regional Government Law, the Environmental Law, the Waste Law, and various other regulations. However, in reality waste management in Indonesia is still very dependent on the end pipe system, where waste is collected, transported and processed to the Final Disposal Site (TPA). This causes the accumulation of waste in very large quantities in the TPA which can harm the environment or even humans around it. Whereas in the Waste Law it is explained that one way to handle waste is to reduce waste by recycling or reusing it.